Enhancing patient-centred communication across barriers: The case of intersubjectivity management in medical interpreting. Issue 7 (July 2022) - Xu, Xinyue; Bridges, Susan M.
Highlights: This article introduces intersubjectivity management to re-conceptualise the practices of medical interpreting in multilingual dental visits. Ad hoc interpreters adopt discursive strategies of intersubjectivity management dynamically according to the exigencies of the ongoing situation. These strategies can enable mutual understanding and promote positive interpersonal relationships between the clinician and patient. The strategies effectively serve to facilitate patient-centred communication. Abstract: Objective: This study introduces the concept of intersubjectivity management in medical interpreting and identifies relevant interactional strategies employed by the interpreter, also explores their effectiveness in facilitating positive clinician-patient communication. Methods: We used conversation analysis (CA) to analyse 27 video recordings of interpreter-mediated dental visits, participants involve English-speaking dentists, Cantonese as the first language (L1) patients and bilingual dental surgery assistants (DSA) who also play the role of ad hoc interpreters. Results: The DSA-as-interpreter manages intersubjectivity for the dentist and patient through interactional strategies, such as reformulating action types, redesigning contents and information capacity, summarising and concentrating turns, constantly monitoring the situation and eliciting spoken or unspoken expressions that are medically relevant from both sides to validate them. The strategies effectively enabled and enhanced the mutual understanding and interpersonal alignment between the dentist and patient. More importantly, the DSA constantly orients to patient-centred communication. Conclusion: Although not professionally trained for interpreting, the DSA-as-interpreters demonstrated discursive strategies. The strategies evidently facilitated positive dentist-patient communication and relationships. Practice Implications: The conceptualisation and significant strategies demonstrated by the DSA-as-interpreters could potentially inform the solution of enhancing multilingual health communication in clinical staff training.